Adaptive robust economic dispatch and real-time control of distribution system considering controllable inverter air-conditioner clusters - Chen, Guanhong; Liu, Dong (Frontiers in Energy Research, 2023)
Tremendous number of renewable energy sources (RES) integrated into distribution system, uncertainty of RES power generation brings about significant challenges to dispatch and power balance of distribution system. As countermeasures, this paper proposes an adaptive robust economic dispatch (ARED) model and a real-time control strategy for distribution system, which make full use of adjustable capability of controllable inverter air-conditioner (IAC) clusters. Firstly, concept of adjustable capacity curve (ACC) is developed to accurately quantify the adjustable capacity of IAC cluster. Afterward, a two-stage adaptive robust optimization is formulated for ARED, which comprehensively takes adjustable capacity of IAC cluster and uncertainty of RES into consideration. Meanwhile, solution methodology of ARED is also designed basing on column and constraint generation (C&CG) algorithm, where the master problem is a quadratic programming with quadratic constraints (QCQP), and the max-min sub-problem is reformulated to a mixed integer linear programming (MILP) form by taking advantage of linear duality theory and big-M method. Finally, a novel real-time decentralized control strategy of IAC cluster is also proposed for purpose of hedging against stochastic RES power fluctuation after every round of ARED decision. Results of study case validates the effectiveness of ARED model and real-time control strategy under different uncertainty scenarios of RES power generation.